ENT 530 Social Media Portfolio: The Desa Baker Bomboloni / Nurain Shahrin - Shahrin, Nurain (2020)
This business is owned by Nurain binti Shahrin as a founder and based on sole proprietor. The name of the business is DESA Bakerlicious and we operate in online platform by using Facebook and Whatsapp as a medium of marketing and selling purpose. Furthermore, we have physical shop located at No. 1 Jalan Pinggiran Putra, 43000 Kajang, Selangor. The DESA Bakerlicious was focus more on sell and make “Bomboloni’ that are round in shape but filled with a variety of appetizing flavors. We using a premium product with a high quality in making this ‘Bomboloni’ a yummy one such as Farm Fresh Milk, egg gred A+, bread flour and more. This business is different from others because we sell ‘Bomboloni’ according to the color based on available flavors where it looks more attractive to attract customers from various age. The price for our ‘Bomboloni’ is also very reasonable and the delivery charge depends on customers’ location. So, people from various background will love and buy our “Bomboloni’ because it is affordable and delicious for sure.